Studies on Growth, Productivity and Economics of Rice as Influenced by Diversification of Rice-Based Cropping Systems in Red and Lateritic Soil of West Bengal - Saha, Biswajit; Barik, Arun Kumar; Mandal, Nakul (International Journal of Bio-resource and Stress Management, 2020)
The field experiments were conducted at Agricultural farm of the Institute during 2014-15 and 2015-16 to study growth, yield attributes, yield and economics of rice as influenced by rice-based cropping systems. The experiment, consisted of ten treatments, was laid out in Randomised Block Design with each treatment replicated thrice. Growth attributes of rice were influenced significantly by diversification of crops in various rice-based cropping systems. Rice in rice–lentil–elephant foot yam showed highest growth attributes followed by rice–frenchbean–baby corn and rice–yellow sarson–greengram systems though they were at par with each other. Rice in rice–potato–greengram system exhibited highest number of paniclesm-2 and filled grains panicle-1 followed by rice–lentil–elephant footyam and rice–frenchbean–baby corn system being at par with each other. Highest grain and straw yield of rice was achieved from rice–potato–greengram (4.81 and 6.12 t ha-1, respectively) followed by rice–yellow sarson–greengram and rice–lentil-okra. Gross return, net return and return per rupee investment in rice were not significant during first year but significant response was found during second year where highest gross return, net return and return per rupee investment was found from rice–potato–green gram system (Rs. 86,417 ha-1, Rs. 52,099 ha-1 and Rs. 2.20, respectively) followed by rice–lentil–okra and rice–yellow sarson-greengram though they were at par with each other. Inclusion of legume crops in rice–based cropping systems enhanced grain and straw yield of rice resulting in higher return from the system.